Ethnic minorities in British politics: candidate selection and clan politics in the Labour Party. Issue 11 (18th August 2019) - Akhtar, Parveen; Peace, Timothy
ABSTRACT: In increasingly diverse polities, the question of how minorities engage with national and local political processes is important. In the U.K., the Labour Party has traditionally benefited electorally from ethnic minority communities, often through ethnicity-based voting blocs. However, little attention has been paid to how the Party's candidate selection process is influenced by strategic party membership and nomination. We argue that community clan or kinship (biraderi) networks found amongst British Pakistanis have been mobilised for this purpose. We examine the cases of Bradford and Birmingham with respect to the nominations for Prospective Candidates at both parliamentary and local council level. We show the continued importance of biraderi connections in spite of Labour Party attempts to 'clean up' selection contests through impositions of the National Executive Committee (NEC). Such practices favour the selection of candidates with strong biraderi links and, as such, often marginalise female candidates.